2021
DOI: 10.4028/www.scientific.net/msf.1023.111
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Free Fatty Acid in Low Free Fatty Acid of Mixed Crude Palm Oil (LMCPO): Optimization of Esterification Parameters

Abstract: The objective of this research was to study the optimum condition of esterified oil production from low free fatty acid of mixed crude palm oil (LMCPO) by using a response surface methodology (RSM) with esterification reaction in a batch mode. LMCPO obtained from a vacuum refining process of mixed crude palm oil (MCPO) to extract the partial FFA in oil which was used as a raw materials in a food production. Therefore, remaining FFA of 6.170 wt.% in LMCPO should be reduced to less than 1 wt.% by using esterific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The final product from the esterification procedure is known as esterified refined crude palm oil (ERCPO). Thawornprasert et al 44 reported the procedure for minimizing FFA content in ERCPO through esterification. The esterification reaction is shown in eq 1.…”
Section: Methodsmentioning
confidence: 99%
“…The final product from the esterification procedure is known as esterified refined crude palm oil (ERCPO). Thawornprasert et al 44 reported the procedure for minimizing FFA content in ERCPO through esterification. The esterification reaction is shown in eq 1.…”
Section: Methodsmentioning
confidence: 99%
“…A short incubation time decreases the overall reaction cost, substrate inventory, and also energy requirement. The time of incubation is dependent on factors such as enzyme activity, the quantity of biocatalyst used, co-substrates concentration, temperature, choice of organic solvent, and the degree of shaking, stirring, and sonication that affects mass transfer (Trinh et al, 2018;Esonye et al, 2019;Thawornprasert et al, 2021).…”
Section: Effect Of Timementioning
confidence: 99%